Preparation method of ceramsite foam concrete product
Through the method of modifying ceratops and precisely controlling the proportion, the problem of insufficient strength of traditional ceratops foam concrete products is solved, the balance between lightweight and high strength of ceratops foam concrete is achieved, and multiple properties of the material are improved.
Patent Information
- Application Number
- CN202411715321.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The overall strength of traditional ceramic foam concrete products is not high and the preparation process is complicated, resulting in insufficient stability of the materials and insufficient compressive resistance.
Modified ceramic particles and specific proportion components are used, including modified ceramic particles, cement, basalt fibers, fly ash, foaming agent, waterproofing agent and gas induction agent. By modifying the ceramic particles and precisely controlling the proportion, the adhesion between the ceramic particles and the cement matrix is improved, and the material is cured at a low temperature by adjusting the curing method.
The lightweight and high strength balance of ceramic foam concrete products is achieved, the compressive strength, wear resistance, water resistance and durability of the material are improved, and the self-weight and thermal conductivity of the material are reduced, thereby enhancing the thermal insulation and sound insulation properties.
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, and in particular to a method for preparing a ceramsite foam concrete product. Background Art
[0002] With the growing demand for energy-saving, environmentally friendly and high-performance materials in modern buildings, the limitations of traditional concrete materials have gradually emerged. Although traditional concrete has high strength, it is heavy, has poor thermal insulation and sound insulation performance, and has high carbon emissions during construction, making it difficult to meet the requirements of modern green buildings and efficient construction. Against this background, ceramsite foam concrete, as a new type of building material, has gradually become the focus of industry attention.
[0003] Ceramic aggregate foam concrete products are made of ultra-light ceramsite (ceramsite bulk density is less than 400kg / m 3 ) and foamed concrete (water, cement, admixtures, special cement foaming agent, special accelerator and enhancer) are mixed, molded, wet cut or dry cut, and naturally cured to form a solid product, which can be a ceramsite foamed concrete board or block. Ceramsite foamed concrete is a building material that combines the advantages of light weight, high strength, thermal insulation, sound insulation, etc. It has been more and more widely used in construction, environmental protection and infrastructure construction in recent years.
[0004] Ceramic aggregate is a lightweight aggregate made of clay, shale, coal gangue, etc. as the main raw materials, which is expanded by high-temperature firing. It has the characteristics of low density, high strength, low water absorption, and good fire resistance. As the aggregate of foamed concrete, ceramsite not only significantly reduces the dead weight of concrete, but also gives the material excellent thermal insulation, sound insulation, fire resistance and antifreeze properties. At the same time, foamed concrete forms a large number of evenly distributed tiny bubble structures by introducing foaming agents into the concrete slurry. These bubbles effectively reduce the density of concrete, make the material lighter, and improve the thermal insulation and sound insulation properties. Therefore, the combination of ceramsite and foamed concrete not only solves the shortcomings of traditional concrete in terms of dead weight and thermal insulation performance, but also provides a feasible solution for achieving energy conservation and emission reduction in buildings.
[0005] The Chinese invention patent application with the patent publication number CN108395274A discloses a lightweight and high-strength ceramsite foam concrete and its preparation method. Adding silica fume, fiber, water repellent and other additives to the cement and fly ash system, the light weight and high strength of the prepared concrete can be taken into account at the same time. The Chinese patent with the publication number CN105541394B discloses a foam concrete, including the following components in mass ratio: 25-60% cement mortar, 5-15% water, 1-3% alkaline water agent, 1-3% plasticizer, 1-5% foaming agent, 0.1-5% inorganic salt, 0.5-5% waterproofing agent, 1-10% clay, 3-12% admixture and 5-25% auxiliary materials. Among them, the admixture is octamethyl polyhedral oligomeric silsesquioxane and glass fiber, the water reducer is polycarboxylic acid water reducer, and the plasticizer is epoxy soybean oil.
[0006] However, the existing technology for preparing ceramsite foam concrete has the following shortcomings: (1) Ceramsite foam concrete products are prone to cracking and shrinkage, and their compressive strength, seismic resistance and thermal insulation performance are not outstanding, which limits their application as lightweight concrete in the field of construction processing. (2) The introduction of flocculants can prevent ceramsite from floating, but excessive aggregation of ceramsite may occur, resulting in honeycombs and stone bags, which reduces the overall quality of foam concrete products. (3) The existing preparation method is relatively complicated, and the foam produced has a short dissipation time and is not stable enough. The individual differences of foams are too large, and improper operation can easily have a significant impact on the pore structure of foam concrete. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a ceramsite foam concrete product, so as to solve the problem that the overall strength of the product is not high due to the weak bonding force between the ceramsite and the cement matrix in the traditional ceramsite foam concrete product.
[0008] In order to achieve the above object, the present invention adopts the following technical solution: A ceramsite foam concrete product is prepared from the following components in parts by weight: 10-15 parts of modified ceramsite, 30-40 parts of cement, 0.5-1.2 parts of basalt fiber, 2-4 parts of fly ash, 0.8-1.2 parts of foaming agent, 0.1-0.5 parts of waterproofing agent, 0.1-0.5 parts of air entraining agent and 15-20 parts of water.
[0009] The preparation method of the ceramsite foam concrete product comprises the following steps: (1) Preparation of modified ceramsite Add 0.5%-1% of nano-silicon dioxide particles to the silane coupling agent solution and stir evenly to obtain a soaking solution; Wash and dry the ceramsite and soak it in the soaking solution to ensure that the surface of the ceramsite is fully in contact with the soaking solution so that the nano-silicon dioxide particles and the silane coupling agent can be adsorbed and reacted at the same time. After soaking for 30 to 60 minutes, take out the ceramsite and dry it at 80°C to 100°C for 1 to 2 hours so that the silane coupling agent and the surface of the ceramsite are chemically bonded and the nano-silicon dioxide is firmly adsorbed on the surface of the ceramsite to obtain the pretreated ceramsite. The pretreated ceramsite is soaked in polyacrylate emulsion for 15-30 minutes to ensure that each ceramsite surface is evenly coated with a layer of polyacrylate film. The coated ceramsite is taken out and dried in a drying oven at 60℃-80℃ for 2 hours to ensure that the polyacrylate film is uniform and stable to obtain modified ceramsite.
[0010] (2) Foam preparation Mix sulfide melamine, melamine resin high-efficiency water reducing agent, composite foaming agent (commercially available product), silicone resin polyether emulsion foam stabilizer, and sodium sulfate drought-strengthening agent in a mass ratio of 4:3:2:1:0.5 to obtain a foaming agent; Pour the above-mentioned foaming agent into the hydraulic foaming machine, start the hydraulic foaming machine, and prepare foam; (3) Slurry preparation Add water, cement, basalt fiber, fly ash and the modified ceramsite of step (1) into a mixer, stir the materials evenly, then continue to add waterproofing agent and air entraining agent under stirring conditions, continue stirring for 5-10 minutes, and obtain a mixed slurry with uniform color; (4) Casting Place the mold on a vibrating table, inject the foam from step (2) into the mixed slurry prepared in step (3), mix well and quickly pour into 2 / 3 of the mold, vibrate 60 times, and pour the remaining 1 / 3 after it is basically cooled; (5) Maintenance and demoulding Scrape off the excess slurry on the surface of the mold, and send the formed expanded clay foam concrete blocks together with the mold into the curing box. First, adjust the temperature of the curing box to 5-10℃, the humidity to more than 80%, and let it stand for curing for 40-48 hours; then adjust the temperature to 20-25℃, let it stand for curing for 23-25 hours, then demould it to obtain the initial expanded clay foam concrete product, and place it in the natural environment without spraying water. After the curing is completed, the expanded clay foam concrete product is obtained.
[0011] Furthermore, in step (1), the preparation method of the silane coupling agent solution is: dissolving the silane coupling agent in ethanol or water to obtain a silane coupling agent solution with a concentration of 3-5%.
[0012] Furthermore, in step (1), the raw material ceramsite is one or a combination of bauxite ceramsite, clay ceramsite, shale ceramsite, riverbed mud ceramsite, fly ash ceramsite, and coal gangue ceramsite, and the particle size of the ceramsite is 5 mm-15 mm, preferably 10 mm. The ceramsite is cleaned with water or 5% dilute hydrochloric acid.
[0013] Furthermore, in step (1), the concentration of the polyacrylate emulsion is 10-20%.
[0014] Furthermore, in step (3), the cement is preferably a mixture of 32.5R silicate cement and mineral powder; fly ash is a production waste of thermal power generation, and is composed of active substances such as SiO2 and Al2O3; the waterproofing agent is a water-based silicone waterproofing agent; and the air entraining agent is one or two of sodium rosin acid and triterpenoid saponin. The stirring speed is 150-220rpm.
[0015] The present invention provides a method for preparing ceramsite foam concrete products, which solves the problem of insufficient strength caused by insufficient bonding of traditional ceramsite foam concrete products by composite modified ceramsite, and at the same time, by introducing admixtures, accurately controlling the mix ratio and improving the pouring method, the structural stability is improved and the overall application range is expanded. The present invention has the following beneficial effects: 1. The present invention achieves a balance between light weight and high strength by accurately adjusting the proportions of materials such as ceramsite, cement, fly ash and foaming agent, so that the material maintains both lightness and sufficient bearing capacity.
[0016] 2. The present invention improves the adhesion between ceramsite and cement matrix, enhances the compressive strength and wear resistance of the material, and improves the water resistance and durability of the material through composite modified ceramsite.
[0017] 3. The present invention adjusts the curing method to keep the foamed concrete in a low temperature state during curing, thereby extending the curing time of the slurry. The hydration process of the ceramsite foamed concrete is more complete, the material density is higher and the pores are less, thereby significantly improving the material's compressive and impermeability properties.
[0018] 4. The foam of the present invention is not easy to break during preparation, and the prepared foam is dense and uniform, which greatly improves the heat insulation and sound insulation performance of the foam concrete, while reducing the deadweight of the foam concrete. The thermal insulation performance, structural integrity and stability of the foam concrete are increased, the environmental adaptability is improved, the strength of the foam concrete is improved, and the cracking problem caused during subsequent use is prevented.
[0019] 5. The dry density of ceramsite foam concrete products is 730-830kg / m 3The compressive strength is 4.0-6.0MPa, the mass water absorption is 5-10%, the thermal conductivity is 0.05-0.10W / (m·K), and the performance meets the requirements of the "Foam Concrete Block" JC / T 1062-2022 standard. DETAILED DESCRIPTION Example
[0020] A lightweight ceramsite foam concrete product is prepared from the following components in parts by weight: 12 parts of modified ceramsite, 35 parts of cement, 0.8 parts of basalt fiber, 3 parts of fly ash, 1 part of foaming agent, 0.3 parts of water-based organosilicon waterproofing agent, 0.3 parts of air entraining agent (sodium rosin acid), and 15-20 parts of water.
[0021] The preparation method of the ceramsite foam concrete product is as follows: (1) Preparation of modified ceramsite The silane coupling agent is dissolved in ethanol to obtain a silane coupling agent solution with a concentration of 4%, 0.75% of nano-silicon dioxide particles are added to the silane coupling agent solution, and the mixture is stirred evenly. Ultrasonic dispersion is performed for 10-15 minutes using an ultrasonic device to obtain an immersion solution.
[0022] The surface of the 10mm bauxite was cleaned with water and placed in an 80℃ oven for drying for 15 minutes. Then the ceramsite was soaked in the above soaking solution to ensure that the surface of the ceramsite was fully in contact with the soaking solution, and the nano-silica particles and the silane coupling agent could be adsorbed and reacted at the same time. After soaking for 45 minutes, the ceramsite was taken out and dried at 90℃ for 1.5 hours to chemically bond the silane coupling agent to the surface of the ceramsite, and the nano-silica was firmly adsorbed on the surface of the ceramsite to obtain the pretreated ceramsite; The pretreated ceramsite was soaked in a 15% polyacrylate emulsion for 25 minutes to ensure that each ceramsite surface was evenly coated with a layer of polyacrylate film. The coated ceramsite was taken out and dried in a drying oven at 70°C for 2 hours to ensure that the polyacrylate film was uniform and stable, thereby obtaining the modified ceramsite.
[0023] (2) Foam preparation Mix sulfide melamine, melamine resin high-efficiency water reducing agent, composite foaming agent (commercially available product), silicone resin polyether emulsion foam stabilizer, and sodium sulfate drought-strengthening agent in a mass ratio of 4:3:2:1:0.5 to obtain a foaming agent; Pour the above-mentioned foaming agent into the hydraulic foaming machine, start the hydraulic foaming machine, and prepare foam.
[0024] (3) Slurry preparation Add water, cement, basalt fiber, fly ash and the modified ceramsite of step (1) into a mixer, and rotate the stirring blade at a speed of about 200 rpm. After the materials are evenly stirred, continue to add the waterproofing agent and the air entraining agent under stirring conditions, and continue stirring for 8 minutes to obtain a mixed slurry with uniform color.
[0025] (4) Casting Place the mold on a vibrating table, inject the foam from step (2) into the mixed slurry prepared in step (3), mix well and quickly pour into 2 / 3 of the mold, vibrate 60 times, and pour the remaining 1 / 3 after it is basically cooled.
[0026] (5) Maintenance and demoulding Scrape off the excess slurry on the surface of the mold, and send the formed expanded clay foam concrete blocks together with the mold into the curing box. First, adjust the temperature of the curing box to 8°C and the humidity to more than 80%, and let it stand for 45 hours; then adjust the temperature to 22.5°C, let it stand for 24 hours, then demould it and get the expanded clay foam concrete primary product. Place it in the natural environment without spraying water, and you will get the expanded clay foam concrete product after the curing is completed.
[0027] After 28 days, the dry density of the ceramsite foam concrete product was measured to be 782kg / m 3 The compressive strength is 5.3MPa, the mass water absorption is 8%, the thermal conductivity is 0.081W / (m·K), and the performance meets the requirements of the "Foam Concrete Block" JC / T 1062-2022 standard. Example
[0028] A lightweight ceramsite foam concrete product is prepared from the following components in parts by weight: 10 parts of modified ceramsite, 30 parts of cement, 0.5 parts of basalt fiber, 2 parts of fly ash, 0.8 parts of foaming agent, 0.15 parts of water-based organosilicon waterproofing agent, 0.18 parts of air entraining agent (triterpenoid saponin), and 15 parts of water.
[0029] The preparation method of the ceramsite foam concrete product is as follows: (1) Preparation of modified ceramsite The silane coupling agent is dissolved in water to obtain a silane coupling agent solution with a concentration of 3%, 0.5% of nano silicon dioxide particles are added to the silane coupling agent solution, and the mixture is stirred evenly to obtain a soaking solution.
[0030] The surface of clay ceramsite with a particle size of 5 mm was cleaned with 5% dilute hydrochloric acid and placed in an 80°C oven for drying for 15 minutes. Then the ceramsite was soaked in the above soaking solution to ensure that the surface of the ceramsite was fully in contact with the soaking solution, and the nano-silica particles and the silane coupling agent could be adsorbed and reacted at the same time. After soaking for 30 minutes, the ceramsite was taken out and dried at 80°C for 2 hours to allow the silane coupling agent to chemically bond with the surface of the ceramsite, and at the same time, the nano-silica was firmly adsorbed on the surface of the ceramsite to obtain the pretreated ceramsite; The pretreated ceramsite was soaked in a 10% polyacrylate emulsion for 15 minutes to ensure that each ceramsite surface was evenly coated with a layer of polyacrylate film. The coated ceramsite was taken out and dried in a drying oven at 60°C for 2 hours to ensure that the polyacrylate film was uniform and stable, and the modified ceramsite was obtained.
[0031] (2) Foam preparation Mix sulfide melamine, melamine resin high-efficiency water reducing agent, composite foaming agent (commercially available product), silicone resin polyether emulsion foam stabilizer, and sodium sulfate drought-strengthening agent in a mass ratio of 4:3:2:1:0.5 to obtain a foaming agent; Pour the above-mentioned foaming agent into the hydraulic foaming machine, start the hydraulic foaming machine, and prepare foam.
[0032] (3) Slurry preparation Add water, cement, basalt fiber, fly ash and the modified ceramsite of step (1) into a mixer, and rotate the stirring blade at a speed of about 150 rpm. After the materials are evenly stirred, continue to add the waterproofing agent and the air entraining agent under stirring conditions, and continue stirring for 5 minutes to obtain a mixed slurry with uniform color.
[0033] (4) Casting Place the mold on a vibrating table, inject the foam from step (2) into the mixed slurry prepared in step (3), mix well and quickly pour into 2 / 3 of the mold, vibrate 60 times, and pour the remaining 1 / 3 after it is basically cooled.
[0034] (5) Maintenance and demoulding Scrape off the excess slurry on the surface of the mold, and send the formed expanded clay foam concrete block together with the mold into the curing box. First, adjust the temperature of the curing box to 10°C and the humidity to more than 80%, and let it stand for 40 hours; then adjust the temperature to 20°C, let it stand for 25 hours, then demould it and get the expanded clay foam concrete primary product. Place it in the natural environment without spraying water, and you will get the expanded clay foam concrete product after the curing is completed.
[0035] After 28 days, the dry density of the ceramsite foam concrete product was measured to be 769kg / m 3The compressive strength is 5.1MPa, the mass water absorption is 9.1%, and the thermal conductivity is 0.076W / (m·K). The performance meets the requirements of the "Foam Concrete Block" JC / T 1062-2022 standard. Example
[0036] A lightweight ceramsite foam concrete product is prepared from the following components in parts by weight: 15 parts of modified ceramsite, 40 parts of cement, 1.2 parts of basalt fiber, 4 parts of fly ash, 1.2 parts of foaming agent, 0.5 parts of water-based organosilicon waterproofing agent, 0.5 parts of air entraining agent (sodium rosin acid and triterpenoid saponin in equal proportions), and 20 parts of water.
[0037] The preparation method of the ceramsite foam concrete product is as follows: (1) Preparation of modified ceramsite The silane coupling agent was dissolved in ethanol to obtain a 5% silane coupling agent solution, 1% of nano-silicon dioxide particles were added to the silane coupling agent solution, and the mixture was stirred evenly. Ultrasonic dispersion was performed using an ultrasonic device for 15 minutes to obtain an immersion solution.
[0038] The surface of shale ceramsite with a particle size of 10 mm was cleaned with water and placed in an oven at 80°C for 15 minutes for drying. Then the ceramsite was soaked in the above soaking solution to ensure that the surface of the ceramsite was fully in contact with the soaking solution, and the nano-silica particles and the silane coupling agent could be adsorbed and reacted at the same time. After soaking for 60 minutes, the ceramsite was taken out and dried at 100°C for 1 hour to chemically bond the silane coupling agent to the surface of the ceramsite, and at the same time, the nano-silica was firmly adsorbed on the surface of the ceramsite to obtain the pretreated ceramsite; The pretreated ceramsite was soaked in a 20% polyacrylate emulsion for 30 minutes to ensure that each ceramsite surface was evenly coated with a layer of polyacrylate film. The coated ceramsite was taken out and dried in a drying oven at 80°C for 2 hours to ensure that the polyacrylate film was uniform and stable, thereby obtaining the modified ceramsite.
[0039] (2) Foam preparation Mix sulfide melamine, melamine resin high-efficiency water reducing agent, composite foaming agent (commercially available product), silicone resin polyether emulsion foam stabilizer, and sodium sulfate drought-strengthening agent in a mass ratio of 4:3:2:1:0.5 to obtain a foaming agent; Pour the above-mentioned foaming agent into the hydraulic foaming machine, start the hydraulic foaming machine, and prepare foam.
[0040] (3) Slurry preparation Add water, cement, basalt fiber, fly ash and the modified ceramsite of step (1) into a mixer, and rotate the stirring blade at a speed of about 220 rpm. After the materials are evenly stirred, continue to add the waterproofing agent and the air entraining agent under stirring conditions, and continue stirring for 10 minutes to obtain a mixed slurry with uniform color.
[0041] (4) Casting Place the mold on a vibrating table, inject the foam from step (2) into the mixed slurry prepared in step (3), mix well and quickly pour into 2 / 3 of the mold, vibrate 60 times, and pour the remaining 1 / 3 after it is basically cooled.
[0042] (5) Maintenance and demoulding Scrape off the excess slurry on the surface of the mold, and send the formed expanded clay foam concrete blocks together with the mold into the curing box. First, adjust the temperature of the curing box to 10°C and the humidity to more than 80%, and let it stand for 48 hours; then adjust the temperature to 25°C, let it stand for 23 hours, and then demold it to obtain the expanded clay foam concrete primary product. Place it in the natural environment without spraying water, and the expanded clay foam concrete product will be obtained after the curing is completed.
[0043] After 28 days, the dry density of the ceramsite foam concrete product was measured to be 805kg / m 3 The compressive strength is 5.4MPa, the mass water absorption is 5.5%, and the thermal conductivity is 0.085W / (m·K). The performance meets the requirements of the "Foam Concrete Block" JC / T 1062-2022 standard.
Claims
1. A ceramsite foam concrete product, characterized in that: It is prepared from the following components in parts by weight: 10-15 parts of modified ceramsite, 30-40 parts of cement, 0.5-1.2 parts of basalt fiber, 2-4 parts of fly ash, 0.8-1.2 parts of foaming agent, 0.1-0.5 parts of waterproofing agent, 0.1-0.5 parts of air entraining agent, and 15-20 parts of water; Wherein, the modified ceramsite is prepared by the following method: ① Add 0.5%-1% nano-silicon dioxide particles to the silane coupling agent solution and stir evenly to obtain a soaking solution; ② Wash and dry the ceramsite and soak it in the above soaking solution to ensure that the surface of the ceramsite is fully in contact with the soaking solution so that the nano-silica particles and the silane coupling agent can be adsorbed and reacted at the same time. After soaking for 30 to 60 minutes, take out the ceramsite and dry it so that the silane coupling agent and the surface of the ceramsite are chemically bonded and the nano-silica is firmly adsorbed on the surface of the ceramsite to obtain pretreated ceramsite; ③ Soak the pretreated ceramsite in polyacrylate emulsion for 15-30 minutes to ensure that the surface of each ceramsite is evenly coated with a layer of polyacrylate film, take out the coated ceramsite, dry it, and obtain modified ceramsite.
2. The ceramsite foam concrete product according to claim 1, characterized in that: The preparation method of the silane coupling agent solution is: dissolving the silane coupling agent in ethanol or water to obtain a silane coupling agent solution with a concentration of 3-5%.
3. The ceramsite foam concrete product according to claim 1, characterized in that: The raw material ceramsite is one or a combination of bauxite ceramsite, clay ceramsite, shale ceramsite, riverbed mud ceramsite, fly ash ceramsite and coal gangue ceramsite.
4. The ceramsite foam concrete product according to claim 1, characterized in that: The particle size of the raw ceramsite is 5mm-15mm, and the ceramsite is cleaned with water or 5% dilute hydrochloric acid.
5. The ceramsite foam concrete product according to claim 1, characterized in that: The concentration of the polyacrylate emulsion is 10-20%.
6. The ceramsite foam concrete product according to claim 1, characterized in that: The foaming agent is obtained by mixing sulfide melamine, melamine resin high-efficiency water reducing agent, composite foaming agent, silicone resin polyether emulsion foam stabilizer and sodium sulfate drought strength agent in a mass ratio of 4:3:2:1:0.
5.
7. The ceramsite foam concrete product according to claim 1, characterized in that: The waterproofing agent is a water-based organic silicon waterproofing agent.
8. The ceramsite foam concrete product according to claim 1, characterized in that: The air entraining agent is one or two of sodium rosin acid and triterpenoid saponin.
9. The method for preparing a ceramsite foam concrete product according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Pour a foaming agent into a hydraulic foaming machine, start the hydraulic foaming machine, and prepare foam; (2) adding water, cement, basalt fiber, fly ash and modified ceramsite into a mixer, stirring the materials evenly, adding a waterproofing agent and an air entraining agent under stirring conditions, stirring evenly, and obtaining a mixed slurry; (3) Place the mold on a vibrating table, inject the foam from step (1) into the mixed slurry prepared in step (2), mix well and quickly pour into 2 / 3 of the mold, vibrate, and pour the remaining 1 / 3 of the mold after it is basically cooled; (4) The formed ceramsite foam concrete blocks are placed together with the mold into a curing box. The temperature of the curing box is first adjusted to 5-10°C, the humidity is adjusted to above 80%, and the blocks are left to cure for 40-48 hours. The temperature is then adjusted to 20-25°C, and the blocks are left to cure for 23-25 hours before demolding to obtain a ceramsite foam concrete primary product. The blocks are placed in a natural environment for curing to obtain a ceramsite foam concrete product.
10. The method for preparing a ceramsite foam concrete product according to claim 9, characterized in that: The stirring speed of step (2) is 150-220 rpm.
Citation Information
Patent Citations
a foam concrete
CN105541394B
Light-weight high-strength ceramsite foam concrete and preparation method thereof
CN108395274A
Air-added ceramsite concrete and preparation method thereof
CN104987005A
Emulsion polymerizing modification method for surface of nano ceramic powder
CN1389434A
Red mud-based sewage treatment agent and preparation method thereof, red mud-based ceramsite concrete and preparation method thereof, and applications
US20220143571A1